Leadership Practices Of School Heads In The Last Mile Schools In The Public Elementary Schools - Magistrado, Aldrin; Pardines, Glenn M.; Pardines, Nerissa M.; Altez , Ma. Eloisa A. (PT. BATARI EDU CALYA, 2024)
Receiving a quality education is a constitutional right of every learner across the globe, regardless of the school's location. Its realization lies in the quality of teaching/learning under the management of the school head. In Buenavista District I, six (6) schools belonged to the last mile schools where learning resources are limited. This study determined the leadership practices of school heads in those schools. The self-made questionnaire was utilized to identify the perception of thirty (30) teachers and (6) school heads. The data collected were analyzed using frequency counting, percentage, weighted mean, and t-test to determine the significant difference between the two groups' perceptions and the significant difference between the problems encountered and the solutions offered. The study revealed a significant difference between the perception of teachers and school heads on the leadership practices but no significant difference in the problems encountered on leadership practices and the solution offered.